Some anatomical parameters of the eyes of patients with different stages of glaucoma - O. A. Koroev; A. O. Koroev; N. T. Khabalova (Российский офтальмологический журнал)
Purpose: to study the morphological structures of the eyes of patients with primary open-angle glaucoma (POAG) and to identify the changes characteristic of this disease.Material and methods. We examined 90 patients with various stages of POAG and compensated ophthalmic tonus and 50 patients without glaucoma with ophthalmic pathology not associated with eye hydrodynamic disorders (control group), aged 40 to 81 years and older. In addition to the standard ophthalmological examination, all patients were examined for the curvature of the anterior surface of the cornea and its thickness, the depth of the anterior chamber and the thickness of the lens, the length of the eye axis, the thickness of the retinal nerve fiber layer (RNFL) and the condition of the optic nerve head (ONH), using ophthalmometry, keratotopography, anterior segment analyzer (Pentacam, OCULUS, USA), ultrasound biometry (UD-6000 Tomey, Japan), and optical coherence tomography (OCT).Results. No significant differences in the parameters of ultrasound biometry and pachymetry were revealed between the control group and POAG patients. The only types of data characterizing the glaucoma process were altered parameters of the optic disc and the peripapillary zone of the retina, namely, the thickness of the RNFL. In 81.1 % of glaucoma eyes, temporal excavation was detected, the average RNFL thickness in the temporal segment of the ONH was 44.2 ± 3.0 μm.Conclusion. Ophthalmoscopy and OCT of the ONH and RNFL are the main diagnostic methods that allow obtaining indisputable data on the morphological changes characteristic of POAG. These studies should become mandatory in the diagnosis of glaucoma and monitoring of patients with POAG..